Oil palm EFB/Kenaf fibre reinforced epoxy hybrid composites: dimension stability behaviours - Abd Malek, Farah Hanan; Md. Tahir, Paridah; Jawaid, Mohammad (Institute of Physics Publishing, 2018)
In recent years, natural fibres composites have gained increasing interest as a most promising material in different applications due to its attractive properties such as eco-friendly, cost-effectiveness and light weight. Though extensive research has been made on the performance evaluation of natural fibres composite materials, not much data is available on the dimension stability which restricts their use in exterior applications. In this study, hybrid composites were fabricated by hand lay-up technique by reinforcing oil palm empty fruits bunch (EFB) and kenaf fibre mats with epoxy matrix. Experiments are evaluated to study dimension stability that includes water absorption, thickness swelling, density and void content. Increasing the kenaf fibre into EFB composite totally improves the dimension stability of the hybrid composites thus indirectly leads to reduction in voids compared to oil palm EFB composites which is presented lowest percentage of dimension stability and higher void content.